(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Personalised medicine has gained attention as a result of the advances of genomic research in the last decade. This includes the rise in epigenetic research, which focuses on the environmental influences on the genome and examines biomarkers that might be useful for cancer therapy. This study investigates the epigenetic biomarkers for breast cancer and its risk factor, obesity, and evaluates their relevance for global public health. Methods: A systematic search of articles published from 2005 to May 2015 was performed in PubMed for epigenetic breast cancer marker. An additional literature search was carried out on the epigenetic markers of obesity. Results: The search resulted in 84 articles on breast cancer, which demonstrate the various applications of epigenetic markers for breast cancer diagnostics, prognostics and treatment. Particularly, non-invasive blood-based diagnostic biomarkers and epigenetic therapy could improve the health outcomes of cancer patients using a personalised approach. The 14 obesity-related articles highlight the epigenetic link of disease and risk factors and emphasise the relevance of nutritional influences. Conclusions: Although epigenetics offers many opportunities, new discoveries have to be confirmed first in clinical settings to ensure advantages over traditional methods. Furthermore, before personalised epigenetic therapy can be applied in public health it is crucial to ensure a fair implementation in both high and low-income settings globally.